Is obesity more likely among children sharing a household with an older child with obesity? Cross-sectional study of linked National Child Measurement Programme data and electronic health records - Carol Dezateux; Nicola Firman; Lucy Griffiths; Gill Harper; Marta Wilk; Milena Marszalek (BMJ Publishing Group, 2024)
Background/objectives We identified household members from electronic health records linked to National Child Measurement Programme (NCMP) data to estimate the likelihood of obesity among children living with an older child with obesity.Methods We included 126 829 NCMP participants in four London boroughs and assigned households from encrypted Unique Property Reference Numbers for 115 466 (91.0%). We categorised the ethnic-adjusted body mass index of the youngest and oldest household children (underweight/healthy weight <91st, ≥91st overweight <98th, obesity ≥98th centile) and estimated adjusted ORs and 95% CIs of obesity in the youngest child by the oldest child's weight status, adjusting for number of household children (2, 3 or ≥4), youngest child's sex, ethnicity and school year of NCMP participation.Results We identified 19 702 households shared by two or more NCMP participants (% male; median age, range (years)-youngest children: 51.2%; 5.2, 4.1-11.8; oldest children: 50.6%; 10.6, 4.1-11.8). One-third of youngest children with obesity shared a household with another child with obesity (33.2%; 95% CI: 31.2, 35.2), compared with 9.2% (8.8, 9.7) of youngest children with a healthy weight. Youngest children living with an older child considered overweight (OR: 2.33; 95% CI: 2.06, 2.64) or obese (4.59; 4.10, 5.14) were more likely to be living with obesity.Conclusions Identifying children sharing households by linking primary care and school records provides novel insights into the shared weight status of children sharing a household. Qualitative research is needed to understand how food practices vary by household characteristics to increase understanding of how the home environment influences childhood obesity.